Percutaneous absorption of aromatic amines in rubber industry workers: impact of impaired skin and skin barrier creams. Issue 6 (20th December 2006) - Korinth, G; Weiss, T; Penkert, S; Schaller, K H; Angerer, J; Drexler, H
Abstract : Background: Several aromatic amines (AA) could cause bladder cancer and are an occupational hygiene problem in the workplace. However, little is known about the percutaneous absorption of chemicals via impaired skin and about the efficacy of skin protection measures to reduce internal exposure. Aims: To determine the impact of skin status and of skin protection measures on the internal exposure to AA in workers manufacturing rubber products. Methods: 51 workers occupationally exposed to aniline and o-toluidine were examined. The workplace conditions, risk factors for skin and the use of personal protective equipment were assessed by means of a self-administered questionnaire. The skin of hands and forearms was clinically examined. Exposure to aniline and o-toluidine was assessed by ambient air and biological monitoring (analyses of urine samples and of haemoglobin adducts). Results: Haemoglobin-AA-adduct levels in workers with erythema (73%) were significantly higher (p<0.04) than in workers with healthy skin (mean values: aniline 1150.4 ng/l vs 951.7 ng/l, o-toluidine 417.9 ng/l vs 118.3 ng/l). The multiple linear regression analysis showed that wearing gloves significantly reduced the internal exposure. A frequent use of skin barrier creams leads to a higher internal exposure of AA (p<0.03). However, the use of skincare creams at the workplace was associated with a reduced internal exposure (p<0.03). From these findings we assume that internal exposure of the workers resulted primarily from the percutaneous uptake. Conclusions: The study demonstrates a significantly higher internal exposure to AA in workers with impaired skin compared with workers with healthy skin. Daily wearing of gloves efficiently reduced internal exposure. However, an increased use of skin barrier creams enhances the percutaneous uptake of AA. Skincare creams seem to support skin regeneration and lead to reduced percutaneous uptake.